PENGARUH KECENDERUNGAN, KEPUASAN DAN STRATEGI MEREK TERHADAP KESETIAAN MEREK PADA USAHA COFFEE SHOP INDEPENDEN - Pangaribuan*, Patriot; Yugopuspito, Pujianto (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
Coffee is a favorite drink for people in general. The coffee industry, especially coffee shops, is increasing and growing from year to year. This study aims to determine the effect of brand strategy consisting of brand ambassadors and brand trust, brand preference, and brand satisfaction on brand loyalty at the Independent Specialty Coffee Shop in increasing sales. The survey was conducted with 385 respondents. This type of research uses quantitative methods and data collection is carried out by distributing online questionnaires containing 20 questions on a Likert scale from 1 to 7. All questions are valid and reliable for further analysis. Data were analyzed by SEM method using the SmartPLS application. The results showed that brand ambassador, -brand-trust, brand preference, and brand satisfaction partially and simultaneously had a positive and significant influence on brand loyalty at the Independent Specialty Coffee Shop, so there was no variable that had no effect. Keywords: Brand Ambassador, Brand Trust, Brand Preference, Brand Satisfaction, Brand Loyalty